Proofs of Prophecy and the Refutation of the Isma'iliyya: the Kitab Ithbat nubuwwat al-nabi by the Zaydi al-Mu'ayyad bi-Ilah al-Haruni (d. 411/1020) - Lika, Eva-Maria (Welten des Islams - Worlds of Islam - Mondes de l'Islam, 2017)
Frontmatter --Acknowledgements --I. Introduction --II. Description of the Manuscripts and the Principles of Edition --III. The Historical Context --IV. Intellectual Defence 1: Criticism of the Ismāʿīliyya --V. Intellectual Defence 2: Prophetology --VI. Conclusion --Bibliography --Index --Critical Edition of the Ithbāt nubuwwat al-nabī by al-Muʼayyad bi-llāh al-Hārūnī